2022
DOI: 10.1002/wcs.1610
|View full text |Cite
|
Sign up to set email alerts
|

Defining attention from an auditory perspective

Abstract: Attention prioritizes certain information at the expense of other information in ways that are similar across vision, audition, and other sensory modalities. It influences how-and even what-information is represented and processed, affecting brain activity at every level. Much of the core research into cognitive and neural mechanisms of attention has used visual tasks. However, the same top-down, object-based, and bottom-up attentional processes shape auditory perception, largely through the same underlying, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 100 publications
0
0
0
Order By: Relevance
“…Such spatial auditory selective attention occurs through coordinated activity in multiple areas of the brain, including prefrontal cortex, parietal cortex, and auditory cortex (Alho et al, 2014; Choi et al, 2014; Deng et al, 2019, 2020; Noyce et al, 2022). Attention modulates the information represented in auditory cortex, enhancing the representation of a target and suppressing the representation of maskers (Noyce et al, 2021; Auerbach and Gritton, 2022). Spatial auditory attention is less effective in listeners with hearing loss; indeed, performance is inversely correlated with spatial discrimination thresholds (Dai et al, 2018; Bonacci et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such spatial auditory selective attention occurs through coordinated activity in multiple areas of the brain, including prefrontal cortex, parietal cortex, and auditory cortex (Alho et al, 2014; Choi et al, 2014; Deng et al, 2019, 2020; Noyce et al, 2022). Attention modulates the information represented in auditory cortex, enhancing the representation of a target and suppressing the representation of maskers (Noyce et al, 2021; Auerbach and Gritton, 2022). Spatial auditory attention is less effective in listeners with hearing loss; indeed, performance is inversely correlated with spatial discrimination thresholds (Dai et al, 2018; Bonacci et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we propose that magnified ILDs enhance spatial perception of the vocoded / BiCI stimuli, allowing listeners to filter out masker-dominated frequencies / time instances that are perceived as off midline and focus attention on the target. When spatial cues do not meaningfully change the TMR, as in experiments in which only ITDs are manipulated, spatial selective auditory attention allows NH listeners to attend to a target amongst spatially separated maskers (Shinn-Cunningham and Best, 2008;Shinn-Cunningham, 2017;Noyce et al, 2021). Such spatial auditory selective attention occurs through coordinated activity in multiple areas of the brain, including prefrontal cortex, parietal cortex, and auditory cortex (Alho et al, 2014;Choi et al, 2014;Deng et al, 2019Deng et al, , 2020Noyce et al, 2022).…”
Section: Attentionmentioning
confidence: 99%
“…Some studies also found that the frontal cortex could modulate auditory cortical excitability in humans [37] and nonhuman primates [38] . A recent review suggested that at least two similar attention networks exist for visual and auditory modalities [39] . We found that the functional connectivities of the frontalleft-temporal cortex in the alpha (6-10 Hz) band could shape the beta band power in the temporal cortex in the beep-flash paradigm.…”
Section: Frontal Cortex Affected Individual Psss By Modulated Sensory...mentioning
confidence: 99%